Features of Critical Thinking Skills for B1 Level Learners - Sultonova Maftuna Baxtiyarovna (International Journal on Human-Computing Studies, 2022)
Critical thinking is the process of considering ideas in many positions, in accordance with their meaningful connections, comparing them with other ideas. It is the result and the moment in thinking when the critical approach becomes natural through interaction with ideas and information, it is an active process, or stimulated, or happens spontaneously and provides the student with the opportunity to control the information, question it, combine, remake, adapt or reject. The article deals with the issues based on the theory of critical thinking and ways of its developing.